The productivity effects of worker mobility between heterogenous firms - Katja Wolf; Bastian Stockinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Several empirical studies find that worker inflows from more productive or otherwise superior firms increase hiring firms' productivity. We conduct a similar analysis for Germany, using a unique linked employer-employee data set, and ranking sending and hiring establishments by their median wage. We find that inflows from superior (higher-paying) establishments do not increase hiring establishments' productivity, but inflows from inferior establishments seem to. Further analyses suggest this effect is due to positive selectivity of such inflows from their sending establishments. Our findings can be interpreted as evidence of a reallocation process by which the best employees of lower-paying establishments become hired by higher-paying establishments. This process reflects the increasingly assortative pattern of worker mobility in Germany, to which our findings suggest a micro-foundation at the establishment and worker levels.
Keywords: J62; D24; J30; 330